Concerning the Representativeness of Psychiatric Catamnestical Studies - The Influence of Various Approach Strategies on the Response of Former Patients - Steinhart, I.; Bosch, G.; Muhr, Th.; Mohlfeld, E. (Methods of Information in Medicine, 1986)
The possible conclusions reached by catamnestical studies are often significantly restricted because of the lack of representativeness of the sample. The example of an investigation of former patients of the Department of Social Psychiatry proves that positive responses to an interview are influenced by various factors. As expected, patients were more inclined to participate in the research project the closer their discharge was to the time of the project itself. Further, it became clear that various different approach strategies, such as letters, enquiries with the registration authorities, phone calls and house visits, effectively increased the motivation of former patients, and that only this kind of graded registration procedure guarantees motivation leading to a sample representative of the total population. Personal contact plays an especially important role. These empirical findings indicate the necessity of careful planning and implementation of sample collection in catamnestical studies. Without this approach, representative results cannot be expected.
Keywords: Sample Collection; Representativeness; Psychiatric Catamnestical Studies; Response Rate